IMPLICATIONS OF OVERCAPACITY FOR CORRECTIONAL INSTITUTIONS IN INDONESIA - Ilham Panunggal Jati Darwin (Cepalo, 2019)
Overcapacity can simply be influenced by the number of prisoners who enter that is not directly proportional to the prison capacity, the number of prisoners who enter the innumerable amount of prisoners who come out, the number of prisoners in prison that is complicated becomes increasingly protracted, which also affects both prisoners and the countries, Based on this issue, this paper aims to discuss how the implications of overcapacity to correctional institutions in Indonesia, using quantitative research methods with literature studies, conclude due to the problem of overcapacity by several factors, both the Penal Institution debate which is inadequate to the minimum prison. People, as well stigmatised the "villain" can make prisoners return as recidivism, then how the overcapacity impact on the health and mentality of inmates, Noted many prisoners who ended with both disease and suicide, while also increasing broad for the sake of a budget that is increasing every year.